72.1k views
5 votes
This equation is an example of:

This equation is an example of:-example-1
This equation is an example of:-example-1
This equation is an example of:-example-2

1 Answer

2 votes

Answer: Choice A. Distributive property

This is using the idea that if (a+b)(c+d+e), then it distributes to a(c+d+e)+b(c+d+e).

It might help to let y = c+d+e.

(a+b)(c+d+e) = (a+b)y

(a+b)(c+d+e) = y(a+b)

(a+b)(c+d+e) = y*a+y*b

(a+b)(c+d+e) = a*y + b*y

(a+b)(c+d+e) = a*(c+d+e) + b*(c+d+e)

User Elena  Unanyan
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.